Total Protein Requirement of Beef Cattle II: Protein Components - Matt Hersom; Jeffrey N. Carter (EDIS)
Revised! AN168, a 3-page fact sheet by Matt Hersom and Jeffrey N. Carter, provides information on protein components and the qualitative differences in the value of the protein in various feedstuffs. Published by the UF Department of Animal Sciences, April 2010.